An Indefinite War of Attrition: The Biden Administration’s Strategy for the Russo-Ukrainian War - Vladimir Trapara (The Review of International Affairs)
This paper examines the outgoing US Biden administration’s strategy for the Russo-Ukrainian War and the prospects of its revision under the incoming Donald Trump administration. Building on Stephen Kotkin’s characterisation of this strategy as an “indefinite war of attrition”, the author addresses questions about the origins and the meaning of this strategy, alternatives to it proposed by its critics, and its alignment with the broader US grand strategy, offering answers as to whether Biden’s decision to allow Ukraine to use long-range weapons against Russia signifies a strategic shift and what options Trump has to end the war. Analysing Biden’s approach to Ukraine throughout his presidency within the framework of the US grand strategy of liberal hegemony and its corresponding policy towards Russia, the paper concludes that the strategy of an indefinite war of attrition—which offers neither Ukrainian victory nor a compromise peace—is consistent with the liberal-hegemonic primary objective to weaken Russia and remove it from the ranks of great powers and remains unchanged with Biden’s latest decisions. For the Trump administration to contribute to resolving the conflict, an approach combining “interventionist” and “isolationist” perspectives on the current strategy is essential.